Photocycloaddition and Rearrangement Reactions in a Putative Route to the Skeleton of Plicamine-Type Alkaloids - Rimböck, Karl-Heinz; Pöthig, Alexander; Bach, Thorsten (Synthesis, 2015)
Two isoquinolones were prepared, to which an allenyl side chain was linked at position C4 via a stereogenic silyloxy-substituted carbon atom. Intramolecular [2+2] photocycloaddition reactions of these substrates proceeded with high diastereoselectivity and delivered the respective cyclobutanes with an exocyclic methylene group (83% and 49% yield). With the 5,6-dioxoloisoquinolone precursor an unprecedented meta-photocycloaddition was observed as a significant side reaction, which occurred at positions C4 and C8a of the isoquinolone skeleton. The cyclobutane products were, after N-alkylation and transformation into the respective cyclobutanones (22–57%), subjected to various rearrangement reactions. In detail, a direct photochemical rearrangement, thermal and photochemical Beckmann rearrangements, and Baeyer–Villiger oxidation reactions were studied. In all cases, products were found, which resulted from cleavage of the amino-substituted cyclobutane bond, but not from the desired cleavage of the alternative alkyl-substituted cyclobutane bond.
Keywords: alkaloids; cycloaddition; heterocycles; isoquinolones; photochemistry; rearrangements